Answer:
x =
![(3)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/e14yosw5rbprbu04e78upb04bghif5atho.png)
Explanation:
Given
2(6 - 2x) - 2x = 2(5 + x) - 4 ← distribute parenthesis on both sides
12 - 4x - 2x = 10 + 2x - 4 ← simplify both sides
12 - 6x = 6 + 2x ( subtract 2x from both sides )
12 - 8x = 6 ( subtract 12 from both sides )
- 8x = - 6 ( divide both sides by - 8 )
x =
=
![(3)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/e14yosw5rbprbu04e78upb04bghif5atho.png)